MATHEMATICAL MODELING OF THE FORECASTING OF THE CONSTRUCTION WASTE REUSAGE OCCURRENCE - Bereziuk, Oleg; Finyk, Iryna (Scientific Works of Vinnytsia National Technical University, 2023)
Object of the research is building waste, annual volume of the building waste in Ukraine is almost 1 mil. t., and the increment of the land areas, occupied by the building waste is 50000 ha. According to the world practice nearly 90 % of the building waste are to be recycled and reused. That is why, the forecast of the dependence of the construction waste reusage occurrence in various countries of the world on the basic parameters of influence in order to develop the strategy of building waste management is an important scientific engineering problem. The study of the reusage of construction waste occurrence in different countries is carried out by planning the experiment of the second order, applying Box-Wilson method by means of the central composite rotatable design (CCDD), using the developed software, protected by the certificate of the State Registration of the right to the copyright object. Aim of the research is the determination of the regression model for the forecasting of the dependence of the construction waste reusage occurrence in different countries on the basic parameters of impact. Regressional dependence of the forecast of the construction waste reusage occurrence on the basic parameters of impact is obtained: density of the country’s population, amount of the gross domestic product per capita, human development index, average geographical latitude. It is determined that, according to Fishers criterion, the hypothesis of the adequacy of the obtained regression model can be considered to be correct if the validity is 95%. Correlation coefficient is 0.99934, this proves the sufficient reliability of the obtained results. Obtained regressional dependence can be used for the development of the strategy for the building waste management. It was determined, that among the considered factors of impact, the value of gross domestic product per capita has the greatest impact, and the average geographical latitude has the least impact. Response surfaces of the objective function – occurrence of the construction waste reusage and their 2D cross-sections in the planes of the impact parameters are constructed.